Analysis of complete mitogenomes and phylogenetic relationships of Frontopsylla spadix and Neopsylla specialis - Liu, Yafang; Chen, Bin; Lu, Xinyan; Liu, Shuang; Jiang, Dandan; Wang, Xuan; Yi, Lin; Li, Rongyu; Zhang, Quanfu; Wu, Lixian; Yang, Xing (Frontiers in Veterinary Science, 2023)
Fleas represent a group of paramount medical significance, subsisting on blood and acting as vectors for an array of naturally occurring diseases. These pathogens constitute essential elements within the plague biome, exerting deleterious effects on both human and livestock health. In this study, we successfully assembled and sequenced the whole mitochondrial genome of Frontopsylla spadix and Neopsylla specialis using long-range PCR and next-generation sequencing technologies. The mitogenomes of F. spadix and N. specialis both have 37 genes with full lengths of 15,085 bp and 16,820 bp, respectively. The topology of the phylogenetic tree elucidates that species F. spadix is clustered in a branch alongside other members of the family Leptopsyllidae, whereas species N. specialis is a sister taxon to Dorcadia ioffi and Hystrichopsylla weida qinlingensis. It also suggests that Pulicidae form a monophyletic clade, Ctenopthalmidae, Hystrichopsyllidae, Vermipsyllidae form a sister group to Ceratophyllidae/Leptopsyllidae group. The mitochondrial genomes of F. spadix and N. specialis were sequenced for the first time, which will contribute to a more comprehensive phylogenetic analysis of the Siphonaptera order. The foundation for subsequent systematic studies, and molecular biology of fleas was established.